Estudo das práticas de gestão em empresas de Vilhena/RO - Soares, Ricardo Silvestre (2009)
This work is a study about management practices. It's a exploratory and quantitative study and data was collected in a determined moment. The sample ounted with 45 companies in a population of 350, all associated to "Associação Empresarial de Vilhena/RO";. The data was obtained with a closed questionnaire, which was applied to the principal manager of the company. The questions were based in the follow topics: i) management models, ii) company scope, iii) result's evaluation, iv) human resource management and v) management software use. The research's results were: there is balance between the presence of organic and mechanic models; the major part of the companies declares the scope, but almost the same number doesn't declare anything; the management pay more attention to the financial results and almost none to the social and environmental impacts; about the human resource management, the indication is used to recruit and the selection is made by curriculum analyses and interview, the major part of the companies doesn't train their employees, the management follow the performance and give remuneration for that; and, the major part of the companies uses management software. Comparing the theory and the data it's showed that it's important to the companies to incorporate better management practices, like pay more attention to the social and environmental impacts of the company's activities.